2015
DOI: 10.1016/j.tibtech.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous surveillance for biosecurity

Abstract: The global movement of people and goods has increased the risk of biosecurity threats and their potential to incur large economic, social, and environmental costs. Conventional manual biosecurity surveillance methods are limited by their scalability in space and time. This article focuses on autonomous surveillance systems, comprising sensor networks, robots, and intelligent algorithms, and their applicability to biosecurity threats. We discuss the spatial and temporal attributes of autonomous surveillance tec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 50 publications
0
32
0
1
Order By: Relevance
“…As UAVs become increasingly adopted by the ecological community (Anderson and Gaston 2013), the excitement generated must be tempered by considered thought on how best to deploy these revolutionary tools. Such exploratory modeling approaches could be further applied to other automated surveillance devices (Jurdak et al 2015), and to freshwater or marine surveys. We have shown that, while population density and aggregation should inform flight decisions, the magnitude of underlying detection errors is fundamentally important to the appropriate choice of flight plan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As UAVs become increasingly adopted by the ecological community (Anderson and Gaston 2013), the excitement generated must be tempered by considered thought on how best to deploy these revolutionary tools. Such exploratory modeling approaches could be further applied to other automated surveillance devices (Jurdak et al 2015), and to freshwater or marine surveys. We have shown that, while population density and aggregation should inform flight decisions, the magnitude of underlying detection errors is fundamentally important to the appropriate choice of flight plan.…”
Section: Discussionmentioning
confidence: 99%
“…To gain maximum benefit from UAV surveys, there is a need to choose appropriate spatial strategies for their deployment (Jurdak et al 2015). With the relatively recent recognition of UAVs' considerable potential to assist in ecological and environmental monitoring (Koh and Wich 2012, Anderson and Gaston 2013, Linchant et al 2015, as yet scant attention has been paid to how the nature of UAV errors in detecting individuals should influence flight protocols for abundance estimation and monitoring (see Dandois et al 2015 for factors affecting forest structure measurement by UAV).…”
Section: Introductionmentioning
confidence: 99%
“…Drones range from basic models under $2000 to sophisticated multisensor models for six figures of more. Drones are used in several biodiversity applications, including monitoring of forest fire [61], identification of floristic biodiversity of understory vegetation [62], identification of standing dead wood and canopy mortality [63], monitoring invasive species, pests, weeds, and diseases [64], and aerial monitoring of animal species [16,65].…”
Section: Emerging Issuesmentioning
confidence: 99%
“…As an example of designs with a minimum energy consumption, aqueous media sailing robots [46,47] and underwater gliders [39] can be mentioned, which consume energy for motion only when altering the sail shape, wing angle and buoyancy. For an aerial environment, there are aerostats [48] and gliders that use forming thermals for drifting up [49]. For the ground wheeled robots and robots with combined wheel-legged mechanisms, combining legged motion advantages with higher energy efficiency of the wheeled chassis on plain ground are used [50].…”
Section: Introductionmentioning
confidence: 99%